Promise or peril in a warming ocean? An emergent pathway leads North Pacific loggerhead sea turtles into the northern California Current System - Dana K. Briscoe; Larry B. Crowder; George H. Balazs; Jeffrey A. Seminoff; F. Alberto Abreu-Grobois; Philippe Gaspar; Catherine A. Lee Hing; Laura Jim; Masanori Kurita; Masanori Mori; Denise M. Parker; Marc R. Rice; et al. (Frontiers in Marine Science, 2026)
Over recent decades, the eastern North Pacific Ocean (ENP) has undergone significant climate-driven change, characterized by rising sea surface temperatures (SSTs), a northward expansion of the North Pacific Transition Zone (NPTZ), and more frequent marine heatwaves. Juvenile North Pacific loggerhead sea turtles ( Caretta caretta ), a highly mobile species sensitive to environmental variability, have emerged as a sentinel species within the region. When North Pacific loggerheads migrate from the eastern subtropical gyre to coastal habitat, they do so offshore of the Baja California Peninsula, Mexico. Analysis of an extensive satellite tracking data set (n=285,1997–2023) revealed no prior observations of juveniles entering the colder, nutrient-rich waters of the northern California Current System (CCS). However, the gradual northward shift of loggerhead foraging habitat has been observed in parallel with an increasingly oligotrophic NPTZ. In 2024, four of 28 satellite-tracked individuals deviated from historic migratory routes and entered the northern CCS. To understand the physical mechanisms that enabled these novel movements, we integrated SST, chlorophyll-a concentrations, and surface current conditions experienced by these individuals and compared them to historical records within the region. During September-October 2024, these turtles reached 45°N latitude, where they encountered strong eastward flow within the North Pacific Current (NPC), thermally suitable conditions, and enhanced productivity. These conditions created a transient, high-latitude migratory corridor into the northern CCS. While three of these turtles benefited from reaching enhanced forage habitat in the California Current System, one likely suffered cold-stunning upon entry into suboptimal waters. The other 24 turtles remained south of the NPC, in the subtropical gyre. Our study represents the first confirmed use of a new, northern CCS migratory corridor by juvenile North Pacific loggerhead sea turtles. These findings expand on the conceptual framework of the ‘thermal corridor hypothesis,’ which suggests that sea turtles opportunistically exploit anomalously warm conditions to reach foraging habitats along the North American coast. They also emphasize the role of additional environmental drivers, such as advective current systems, in these movements. Under accelerated climate change, such transient pathways may become increasingly prevalent, with significant implications for conservation planning and fisheries management.